Zapomniany film o Barbarze Radziwiłłównie - Monika Werner (Fabrica Litterarum Polono-Italica, 2020)
The article focuses on the first Polish film in which the figure of Bona Sforza appeared, namely Barbara Radziwiłłówna, created by Józef Lejtes, a well-known director, in 1936. Moreover, it discusses the circumstances in which the film was made, and the image of the queen presented therein. Numerous comments which appeared in the press, both contemporary and of a later period, have been recalled.